Dampak Kepengurusan Ganda Pokdarwis: Studi Kasus Desa Wisata Nglanggeran - Nuri, Annisa Nada; Erina, Vania Azra; Saputra, Ferdian Dwi; Nafisa, An'cahya Titin (Pusat Studi Pariwisata Universitas Gadjah Mada, 2025)
The role of local community involvement in the development of tourism activities in tourist villages is a critical aspect. However, issues regarding community participation in these villages are still prevalent. In light of this phenomenon, the present study examines the impact of dual management within the Tourism Awareness Group (Pokdarwis) in Nglanggeran Tourism Village. This research adopts a qualitative descriptive approach, utilizing literature studies and interviews as data collection techniques. The findings of the study reveal the existence of dual management practices that do not comply with the regulations outlined in Governor Regulation No. 40 of 2020, which pertains to the management of Pokdarwis, tourist villages, and village apparatus. These dual management practices are observed in the overlap between the management of Pokdarwis and the management of the tourist village, as well as between Pokdarwis and village officials. Based on the interview data, this dual management phenomenon appears to be a strategy to optimize limited human resources due to challenges in generational succession, while also minimizing potential conflicts between different levels of village management. In light of these findings, the research team recommends that future studies explore the perspectives of the local community regarding Governor Regulation No. 40 of 2020. This recommendation responds to the ongoing issue of dual management in the Nglanggeran Tourist Village.